Hi all,
Could someone please help me quantify the following rules?
(1) (A ⋀ B) → C
(2) (A ⋀ ¬B) → C
(3) (¬A ⋀ B) → C
(4) (¬A ⋀ ¬B) → ¬C
Ultimately I would like to be able to represent the above in set theory notation such that they would read in the following way (respectively):
(1) If A and B coincide, then C (or so too do they coincide with C)
(2) If A coincides with not-B, then C
(3) If not-A and B coincide, then C
(4) If not-A and not-B coincide, then not-C.
Many apologies for the rudimentary query. I'm not versed in formal notation but need to make use of it nonetheless.
With many thanks,
bahen
Could someone please help me quantify the following rules?
(1) (A ⋀ B) → C
(2) (A ⋀ ¬B) → C
(3) (¬A ⋀ B) → C
(4) (¬A ⋀ ¬B) → ¬C
Ultimately I would like to be able to represent the above in set theory notation such that they would read in the following way (respectively):
(1) If A and B coincide, then C (or so too do they coincide with C)
(2) If A coincides with not-B, then C
(3) If not-A and B coincide, then C
(4) If not-A and not-B coincide, then not-C.
Many apologies for the rudimentary query. I'm not versed in formal notation but need to make use of it nonetheless.
With many thanks,
bahen